Leading wisely : becoming a reflective leader in turbulent times - Kets de Vries, Manfred F. R. (John Wiley & Sons Ltd, 2022)
"In these most turbulent of times when enlightened leadership is needed more than ever, relying simply on knowledge, data and information as the sources for our decisions can only direct us toward solutions too superficial to solve the problems before us. We must look instead to ground our leadership in a deeper and more subtle form of discernment--wisdom. As a pioneering practitioner and educator in the field of clinical and psychodynamic-systemic executive coaching, Kets de Vries is in a unique position to shed light on this path. His compact, reflective volume begins with three chapters that lay the foundation for our understanding of wisdom and our grasping of what he calls the 'wisdom equation'. These chapters are followed by eight lessons on wisdom, each focusing on a particular aspect of wisdom or on developing a related skill. Woven throughout are anecdotes and tales from various spiritual and cultural traditions that enrich and give deeper significance to his argument. This small volume serves as an invitation to explore the importance of wisdom as a foundational principle in our lives and a powerful vehicle for generating the kind of reflective leaders most needed in our troubled world."--